Melacak Sejarah Kodifikasi Al-Quran - Ahmad Zaeni (AL-MUFASSIR, 2021)
The article discusses the history of the codification of the Qoran since the time of the Prophet until it was recorded as a mushaf during the time of Khulafa al-Rashidin. The urgency of this study is to emphasize that historically, the authenticity of the Koran has been guaranteed since its revelation. This study is qualitative in nature using the documentation method (al-manhaj al-tausiqi) and historical method (al-manhaj al-tarikhi) The results of this study are, there are 3 stages of writing the Qoran, first, writing during the revelation on various simple written media and still separate from one another, but the order of verses and letters has been determined by the Prophet. Second, the codification of the Koran into one volume of the Mushaf at the time of Caliph Abu Bakr. The three copies of the Mushaf in the time of Usman bin Affan were to maintain a valid qiraat in response to dialect differences